2012
DOI: 10.1007/s00210-012-0798-z
|View full text |Cite
|
Sign up to set email alerts
|

Euterpe oleracea Mart.-derived polyphenols prevent endothelial dysfunction and vascular structural changes in renovascular hypertensive rats: role of oxidative stress

Abstract: The consumption of polyphenol-rich foods is associated with a decreased risk of mortality from cardiovascular diseases. Previously, we have demonstrated that the stone of Euterpe oleracea Mart. (açaí) from the Amazon region exerts vasodilator and antioxidant actions. This study examined the effect of açaí stone extract (ASE) on the vascular functional and structural changes and oxidative stress associated with the two-kidney, one-clip (2K-1C) renovascular hypertension. 2K-1C and sham-operated rats were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 56 publications
5
53
1
5
Order By: Relevance
“…Several studies demonstrated that açaí possesses high levels of phytochemicals with antioxidant, antinociceptive, anti-inflammatory, hypocholesterolemic, and anticancer activities [2026,35,36]. To our knowledge, this report is the first study to evaluate the anti-inflammatory and antiangiogenic effects of açaí in endometriotic implants.…”
Section: Discussionmentioning
confidence: 86%
“…Several studies demonstrated that açaí possesses high levels of phytochemicals with antioxidant, antinociceptive, anti-inflammatory, hypocholesterolemic, and anticancer activities [2026,35,36]. To our knowledge, this report is the first study to evaluate the anti-inflammatory and antiangiogenic effects of açaí in endometriotic implants.…”
Section: Discussionmentioning
confidence: 86%
“…Da Costa et al demonstrated increase of CAT, superoxide dismutase and glutathione peroxidase after oral administration of Açai stone extract to renovascular hypertensive rats. 30 Also the antioxidant effect of Açai has been demonstrated in other organs like brain, 12 lungs, 31 liver 32 in experimental animals. In addition, consumption of Açai pulp and juice was associated with increased plasma antioxidant capacity in healthy human volunteers.…”
Section: Discussionmentioning
confidence: 98%
“…Such improvement was attributed according to the researchers to the significant proven antioxidant effect of Açai. 30 …”
Section: Discussionmentioning
confidence: 99%
“…After defrosting at room temperature, fruits were separated into three portions: bark, seed and total fruit (bark + seed). The procedures used to prepared the hydroalcoholic extracts have been described previously [3]. Briefly, about 360 g of each different portion were washed in running water and boiled in distilled water for 5 minutes.…”
Section: Methodsmentioning
confidence: 99%